The Role of Environmentally Friendly Practices in the Palm Oil Industry: Encouraging Green Product Production in West Sumatra - Candrianto Candrianto; Isra Mouludi; Ester Edwar (Green Publisher Indonesia, 2026)
The palm oil industry plays a strategic role in supporting economic growth in Indonesia, particularly in regions such as West Sumatra. However, the rapid expansion of palm oil processing activities has also generated serious environmental challenges, including liquid, solid, and gas waste that may negatively affect ecosystems if not managed properly. Therefore, environmentally friendly practices have become increasingly important to support sustainable industrial development and encourage the production of green products. This study aims to analyze the role of environmentally friendly practices in the palm oil industry in encouraging green product production in West Sumatra. The research employed a qualitative approach by collecting data through interviews, observations, documentation studies, and literature reviews related to sustainable palm oil management. The collected data were analyzed using qualitative descriptive analysis to identify patterns and relationships between environmental practices and green product development. The findings reveal that the implementation of environmentally friendly practices based on Knowledge Management System (KMS) and ecopreneur principles significantly contributes to environmental sustainability and product competitiveness. Effective waste management, the use of environmentally friendly materials, recycling activities, and eco-labeled product development support the creation of sustainable products with higher market value. In conclusion, environmentally friendly practices not only reduce environmental impacts but also strengthen the competitiveness and sustainability of the palm oil industry in West Sumatra.